O policiamento baseado em evidências e a dinâmica atual de controle da criminalidade na cidade de Manaus - Santos, Moisés Israel Silva Dos (2019)
Evidence-based policing presents itself as a management model in which data analysis, information gathering and intelligence generation are essential for an objective decision making model that corroborates the elucidation, control and deterrence of crime in previously determined areas. This model uses two types of research: the basic one, identifying what works best when implemented correctly and the search for results found after implantation. The general objective of this research is to identify and analyze how the evidence-based policing model has been used in the control and deterrence of crime in the city of Manaus, through the review of the police literature about the origin and development of the police throughout history, while relate the criminological theories that involve the theme, and, when studying the evidence-based policing model and its application. It was found that the concentration of crimes in places and times through the use of maps and spatial analysis software demonstrates that this study can support / subsidize the process of formulating, implementing and evaluating police actions. It is proposed that evidence-based policing translates into an effective tool for the control and deterrence of crime, since in the places where it has been implemented it has been found that it is an eminent option in the management of policing to enhance the existing means of employment and execution of planned actions.